Muszlim források a honfoglalás előtti magyarokról. - Zimonyi, István.
1 online resource.
Keywords: The Jayhānī tradition contains the most detailed description of the Magyars/Hungarians before the Conquest of the Carpathian Basin (895). Unfortunately, the book itself was lost and it can only be reconstructed from late Arabic, Persian and Turkic copies. The reconstruction is primarily based on the texts of al-Marwazī, Ibn Rusta and Gardīzī. The original text has shorter and longer versions. The basic text was reformed at least twice and later copyists added further emendation. This study focuses on the philological comments and historical interpretation of the Magyar chapter, integrating the results in the fields of medieval Islamic studies, the medieval history of Eurasian steppe, and the historiography of early Hungarian history.